Transient leukaemia of Down syndrome in a neonate: case report - Bhaisara, Baraturam; Korday, Charusheela; Wade, Minal; Chunchu, Chandra Kiran; Modi, Priyanka; Singh, Dinesh Kumar (International Journal of Contemporary Pediatrics, 2019)
Transient leukemia of Down syndrome(TL-DS) or transient myeloproliferative disorder (TMD) or transient abnormal myelopoiesis (TAM) is a hematologic abnormality characterized by an uncontrolled proliferation of myeloblasts in peripheral blood and bone marrow which characteristically affects newborns and babies with Down syndrome. Children with Down syndrome (Trisomy 21) have a unique predisposition to develop myeloid leukemia of Down syndrome(ML-DS). In majority of cases of TL-DS, the GATA1 mutant clone goes into spontaneous remission without the need for chemotherapy. However, 10-20 % of neonates with TL-DS and silent TL-DS subsequently develop ML-DS in the first 5 years of life due to additional oncogenic mutations acquired by the persistent GATA1 mutant cells. We present here, one such case of Down syndrome with TL-DS in a neonate.